Titanium Self‐Intercalation in Titanium Diselenide Devices: Insights from In Situ Transmission Electron Microscopy - Sung, Hsin‐Ya; Wang, Che‐Hung; Lee, Mu‐Pai; Lin, Yu‐Chuan; Lin, Yen‐Fu; Huang, Chun‐Wei; Wu, Wen‐Wei (Advanced materials (Weinheim), 2025)
Metallic transition metal dichalcogenides (MTMDCs) are of significant attention for various electronic applications due to their anisotropic conductivity, high electron mobility, superconductivity, and charge‐density‐waves (CDW). Understanding the correlations between electronic properties and structural transformations is crucial. In this study, a bias‐induced structural transformation in vertical CDW‐based 1T‐TiSe2 devices, transitioning from a 1T metallic phase to a distorted transition 1Td phase and subsequently to an orthorhombic Ti9Se2 conducting phase, is reported. Using ex‐situ and in‐situ biasing transmission electron microscopy, dynamic structural changes, while electron energy loss spectroscopy analysis revealed valence state modifications in Ti and Se within the Ti‐rich layer after biasing, are observed. In addition, the effect of varying 1T‐TiSe2 thickness on the maximum current value is investigated. These observations reveal that increased thickness requires higher voltage to induce phase transitions. These insights contribute to understanding the structural and electronic dynamics of 1T‐TiSe2, highlighting its potential as a promising material for future CDW‐based device applications. This study investigates bias‐induced structural transformations in 1T‐TiSe2 devices, focusing on the transition from the 1T metallic phase to the distorted 1Td phase and ultimately to an orthorhombic Ti9Se2 conducting phase. Using ex‐situ and in‐situ TEM, dynamic structural changes and insights into the effect of thickness on phase transitions, providing valuable information for CDW‐based device applications, are revealed.